Application of Mutual Storytelling Techniques in Overcoming Sibling Rivalry in Client "A" - Meithiya, Annisa Sri; Noviza, Neni; Putra, Bela Janare; Ramčilović, Zećir; Hijazi, Muhammad; Abrori, M. Sayyidul (Grief and Trauma, 2024)
This research aims to explore the condition of sibling rivalry experienced by client "A" and examine the application of the mutual storytelling technique in addressing it. Sibling rivalry is a common issue where competition between siblings arises, often fueled by factors such as perceived parental favoritism, jealousy, and a competitive spirit. Client "A" exhibits several characteristics of sibling rivalry, including aggressive behavior, resentment, anger, and feelings of envy towards their sibling. Through this study, the researcher seeks to understand the dynamics of sibling rivalry in client "A" and how the mutual storytelling technique can be applied to help mitigate these behaviors. The research adopts a qualitative approach with a case study method, utilizing observation, interviews, and documentation as data collection techniques. The data analysis involves pattern matching, explanatory analysis, and time series analysis to comprehensively examine the case. The findings provide insight into client "A's" rivalry, characterized by aggression and a competitive attitude, and explore how mutual storytelling can be a useful tool for addressing these issues.